Electrochemical Hydrogen Storage Properties of Sintered La0.7Mg0.3Ni2.5Co0.4Mn0.2Al0.1 Alloy - Ma, Yanchun; Wang, Xiaolin; Dong, Zhenwei; Wu, Yaoming; Wang, Limin; Zhu, Jianwei (Asian Journal of Chemistry, 2013)
The La0.7Mg0.3Ni2.5Co0.4Mn0.2Al0.1 hydrogen storage alloy was synthesized by arc-melting and powder sintering techniques and the microstructure and electrochemical performance of the alloy were investigated. The results showed that the alloy mainly consist of the (La, Mg) Ni3 and the LaNi5 phases and the powder sintering time made a different effect on the electrochemical hydrogen storage properties, when the alloy sintered at 1173 K for 4 h, it exhibited a maximum discharge capacity of 334 mAh/g and the sintered alloy for 10 h showed a best cyclic stability, the cycling capacity retention rate was 69.1 % after 100 cycles.